The Effectiveness of Herbal Plant Extracts in Burn Wound Care: A Systematic Literature Review - NURLELA PETRA SARAGIH; Chrismis Novalinda Ginting; Tiarnida Nababan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Background: Burns are tissue injuries caused by various thermal, chemical, or electrical agents, resulting in serious skin damage that requires comprehensive management. Traditional burn care often utilizes herbal plants due to their bioactive compounds, which have the potential to accelerate the healing process and reduce complications. Objective: This study aims to systematically examine the effectiveness of various medicinal plant extracts in accelerating the healing of Grade I and II burns, based on evidence from relevant experimental studies. Method: The research methodology follows the PRISMA guidelines, employing a literature review to identify experimental studies evaluating the efficacy of medicinal plant extracts in burn management published between 2019 and 2025 in both Indonesian and English. The search process utilized electronic databases such as Google Scholar and ResearchGate, using a combination of keywords including "Luka Bakar" OR "Burn Healing" OR "Wound of Burn," "herbal," "tanaman herbal," "rats," and "Wistar." From the 10,800 articles identified, after removing duplicates and initial screening based on titles and abstracts, 10,718 articles underwent further screening based on full-text availability, publication year (2019-2025), language, and relevance. Ultimately, 14 studies were selected for review. Results: Data from various studies indicate that the application of full-concentration (100%) aloe vera gel provides optimal burn healing results, with a success rate reaching 95.99% within a 12-day period. Conclusion: The use of medicinal plants demonstrates promising therapeutic prospects for the treatment of mild to moderate burns (Grade I and II), owing to their ability to shorten healing duration and reduce associated morbidity.